A case study of the group work management techniques of an English second language teacher in the Molopo circuit of Bophuthatswana - Alfers, Helen Joy (Rhodes University, Faculty of Education, Department of Education, 1994)
This study examines the small group work management techniques of a teacher of English in a second language classroom in Bophuthatswana. The school at which the observation takes place, is a black secondary school in Mmabatho which follows the Department of Education and Training (DET) syllabus and writes the DET external matriculation examination. The goal of the research is to assess and evaluate the methods the teacher uses in managing group work according to five specified areas. These areas are noted for their importance in the successful management of group work. The report on the findings of this research reveals that the teacher's understanding of the nature of small group work differs from the accepted characteristics of successful group work management as interpreted by authorities in this field. This gives rise to management techniques that are sometimes inappropriate and ill-considered. Although this study observes only one teacher, the findings indicate the need for more classroom-based research in order to establish the true nature of classroom practice. Assumptions about classroom practice are too readily made by innovators, syllabus designers and textbook writers who design materials based on methodologies which can be complex and difficult to implement. These methodologies require understanding and commitment from the teacher. However, the pre-service and in-service education and development that the teacher receives often does not guarantee understanding of the processes involved nor does it generate the necessary commitment to small group work as an effective teaching technique.
Keywords: English language -- Study and teaching -- South Africa -- Bophuthatswana--Foreign speakers